Personalization as an Editorial Strategy in the Coverage of Political Scandals: The Case of the Spanish Monarchy - Ortiz-González, Azahara; Berganza, Rosa (Estudios sobre el Mensaje Periodístico, 2023)
Analysis of the use of personalization in journalistic content about political corruption scandals is scarce. From that, the objective of this investigation: study its use as a political-editorial strategy on printed and digital Spanish media in the coverage of scandals. The analysis is based on the measure of different variables created by Just and Crigler (2019) and Van Aelst et al. (2012) applied to a study case: the scandals of the Emeritus King of Spain, Juan Carlos I. To do so, qualitative content analysis is carried out on 334 journalistic pieces published by five different media. Results show that responsibility is mainly attributed to the emeritus king and not the monarchy, although the differences between media are relevant depending on their editorial position. elDiario.es and El Español are the ones who attribute the most the responsibility to the monarchy.